Growth performance and nutritional status of Hevea brasiliensis planted on two types of soil. - Wan Daud, Noordin; Mokhatar, Shafar Jefri (2014)
Hevea brasiliensis or rubber tree has been planted on marginal soil due to competition with other crops and infrastructure development. Objective of this study was to assess the nutrient uptake of rubber tree in relation to different soil textures. RRIM 2001, RRIM 2025 and RRIM 3001 clones were used and Munchong and Holyrood as soil series tested. Several physical and chemical properties of soil were analyzed before the study. Fertilizer was applied at current recommendation rate, 18.75 kg/ha. After a year, growth indicator; height, girth was measured and leaves nutritional status were analyzed. Texture of these soils influenced the chemical properties of the soil. Holyrood series has lower CEC than Munchong series which retained much lower nutrient applied from the fertilizer available for plant. From leaf nutrient analyzed, plant grown on Holyrood significantly showed lower value compared to plant grown on Munchong. It can be concluded that Munchong series is much better than Holyrood series in providing nutrient for plant uptake and growth. RRIM 3001 showed higher performance than RRIM 2001 and RRIM 2025.